2018
DOI: 10.1002/bmc.4238
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of cystine in human renal proximal tubule cells using liquid chromatography–tandem mass spectrometry

Abstract: Nephropathic cystinosis is characterized by abnormal intralysosomal accumulation of cystine throughout the body, causing irreversible damage to various organs, particularly the kidneys. Cysteamine, the currently available treatment, can reduce lysosomal cystine and postpone disease progression. However, cysteamine poses serious side effects and does not address all of the symptoms of cystinosis. To screen for new treatment options, a rapid and reliable high‐performance liquid chromatography–tandem mass spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Its levels in biological samples are commonly measured by SRM. The SRM transition 241→74 [ 4 , 10 , 12 , 13 , 22 ] or 241→152 [ 6 , 7 , 8 , 9 , 11 , 22 ] is mostly used for cystine quantification to increase sensitivity. Our data showed that the m/z 152 fragment ion was predominant when the collision energy was low ( Figure 2 a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Its levels in biological samples are commonly measured by SRM. The SRM transition 241→74 [ 4 , 10 , 12 , 13 , 22 ] or 241→152 [ 6 , 7 , 8 , 9 , 11 , 22 ] is mostly used for cystine quantification to increase sensitivity. Our data showed that the m/z 152 fragment ion was predominant when the collision energy was low ( Figure 2 a).…”
Section: Resultsmentioning
confidence: 99%
“…Cystine in urine, blood, or other biological samples has been used as an important biomarker for various pathological conditions, such as inherited metabolic disorders and cystinosis [ 4 , 5 , 6 ]. Quantification of cystine in leukocytes and urine by CID-based LC–MS/MS is performed in the clinical routine for diagnosis of nephropathic cystinosis [ 7 , 8 , 9 , 10 ]. Selected reaction monitoring (SRM) is the mostly reported method for measuring cystine [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with the increased TFEB activity, bicalutamide also restored endocytic cargo processing in cystinotic cells (Fig 5D and E), allowing us to test whether the increased degradation of lysosomal cargo results in decreased cystine accumulation. We used a more sensitive and quantitative LC-MS/MS method (Jamalpoor et al, 2018) to measure cystine levels in cystinotic cells upon treatment with cysteamine, bicalutamide, or their combination. In line with metabolomics data, CTNS À/À cells treated with bicalutamide alone did not exhibit any reduction in cystine levels.…”
Section: Alpha-ketoglutarate Regulates the Phenotypic Alterations In Cystinosismentioning
confidence: 99%
“…Cystine levels were quantified using high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS); a rapid and sensitive assay that has been developed and validated in house. 22 In brief, cell pellets were suspended in N-Ethylmaleimide (NEM) solution containing 5 mM NEM in 0.1 mM sodium phosphate buffer (pH 7.4). The cell suspension was then precipitated, and protein was extracted with sulfosalicylic acid 15% (w/v) and centrifuged at 20,000 g for 10 min at 4 o C. Protein concentration was determined by the method of the Pierce™ BCA protein assay kit according to the manufacturer's protocol (Thermo Fisher, The Netherlands), and the cystine concentration was measured using HPLC-MS/MS.…”
Section: Intracellular Cystine Quantification By Hplc-ms/msmentioning
confidence: 99%